Psikoedukasi Sekolah Ramah Anak Di Desa Pasirtanjung Kabupaten Bogor - Issom, Fitri Lestari; Suryaratri, Ratna Dyah; Rustyawati, Reny (Universitas Negeri Jakarta, 2023)
This community service activity aims to implement Child Friendly School psychoeducation in the Pasirtanjung area. This psychoeducation will focus on discussing children's rights to build discipline, character and positive communication between school members. It is expected that with this psychoeducation, teachers can fulfill, guarantee and protect children's rights, and ensure that schools are able to develop children's interests, talents and abilities. In addition, schools are expected to not only give birth to a generation that is intellectually intelligent, but also to give birth to a generation that is emotionally and spiritually intelligent. In seeking to increase this awareness, teachers are involved in this community service activity, which has several activities in it. Activities in the form of psychoeducation delivered in the form of seminars through material presentation, video screening, practice and questions and answers related to the material. Child Friendly School psychoeducation activities at Madrasah Ibtidaiyah Man'baul Islamiyah, Pasirtanjung Village, Bogor Regency run according to the specified schedule and this activity is right on target because the school has never received Child Friendly School socialization from the government. This psychoeducation is also proven to add a new understanding for teachers about the concept of Child Friendly Schools and how to implement it, as evidenced by the improvement results from the pretest and posttest.